What Is the Role of AI in Telepsychiatry? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The global burden of mental health disorders has become one of the most pressing public health challenges of our time, a situation dramatically intensified b...
Keywords: Telemedicine and Digital Health; Telepsychiatry; Artificial Intelligence; Machine Learning; Healthcare; Diagnostics